Organizational Environment Research: Methodology Proposed to a Higher Education Institution from Serra Gaucha - de, Juliana Raquel; ., Maria Emilia Camargo (Information Management and Business Review, 2012)
The people who form them differentiate the organizations and it is because of that the competitiveness is fierce nowadays. The environment organization research is a formal method to evaluate the environment of a company and it is an important instrument to provide subsidies, which allow the constant improvement of the work environment. Therefore, we propose the study of the organizational environment through the construction of a research instrument applied to the teachers of the Department of Administration from a Higher Institution at Serra Gaucha. The objective is to identify the aspects related to the commitment in the accomplishment of the job and the improvement on the quality of the provided services and to verify if the punctuation of the factors diverges. After the application of the questionnaire, we can observe that the mean values of the opinion regarding the categories (Institutional Image, Institutional Politics, System of Assistance and Benefits, Organization Structure, Organization and Work Condition, Interpersonal Relationship, Leadership Behavior, Personal Satisfaction, Institutional Planning, Decisive Process, University Autonomy and Institutional Evaluation) of respondents is good, because the averages are, in most cases, above the value 3 (the scale ranges from 1 to 5). The one that had an average below 3 was referred to the decision process. The mean general was 3.6. We can observe that the mean values of the opinion regarding the categories of respondents are good, because the averages are, in most cases, above the value 3 (the scale ranges from 1 to 5). The one that had an average below 3 was referred to the decision process. The mean general of respondents was 3.6.